Concurrent vision and hearing impairment associated with cognitive dysfunction in a population aged 85+ years: the Ural Very Old Study - Bikbov, Mukharram M; Kazakbaeva, Gyulli M; Rakhimova, Ellina M; Rusakova, Iuliia A; Fakhretdinova, Albina A; Tuliakova, Azaliia M; Panda-Jonas, Songhomitra; Bolshakova, Natalia I; Safiullina, Kamilia R; Gizzatov, Ainur V; Ponomarev, Ildar P; Yakupova, Dilya F; et al. (BMJ open, 2022)
ObjectiveTo assess the prevalence of vision impairment, hearing impairment and dual sensory impairment (DSI) as combination of vision and hearing impairment, in association with cognitive dysfunction in a population aged 85+ years.MethodsThe cross-sectional population-based Ural Very Old Study, conducted in rural and urban Bashkortostan, Russia, between 2017 and 2020, included a detailed ocular and systemic examination with assessment of moderate to severe vision impairment (MSVI)/blindness (best-corrected visual acuity <6/18), moderate to severe hearing loss (MSHL) and cognitive function.SettingA rural and urban area in Bashkortostan, Russia.ParticipantsOut of 1882 eligible individuals aged 85+ years, 1526 (81.1%) individuals participated.Primary and secondary outcome measuresPrevalence of vision, hearing and DSI and cognitive dysfunction.ResultsThe study included 731 (47.9%) individuals (mean age 88.1±2.7 years; median 87 years, range 85–98 years) with measurements of MSVI/blindness, MSHL and cognitive function. The prevalence of MSVI/blindness, MSHL, DSI and dementia were 51.8% (95% CI 48.2% to 55.5%), 33.1% (95% CI 29.7% to 36.5%), 20.5% (95% CI 17.8% to 23.5%) and 48.2% (95% CI 44.5% to 51.8%), respectively. Lower cognitive function score was associated with lower visual acuity (p<0.001) and higher hearing loss score (p=0.03), after adjusting for older age (p=0.001), rural region of habitation (p=0.003), lower educational level (p<0.001) and higher depression score (p<0.001). Higher dementia prevalence was associated with higher MSHL prevalence (OR 2.18 95% CI 1.59 to 2.98; p<0.001), higher MSVI/blindness prevalence (OR 2.09, 95% CI 1.55 to 2.81; p<0.001) and higher DSI prevalence (OR 2.80, 95% CI 1.92 to 4.07; p<0.001).ConclusionsIn this very old, multiethnic population from Russia, DSI (prevalence 20.5%), as compared with hearing impairment (OR 2.18) and vision impairment alone (OR 2.09), had a stronger association (OR 2.80) with dementia. The findings show the importance of hearing and vision impairment, in particular their combined occurrence, for dementia prevalence in an old population.